MENDETEKSI FINANCIAL STATEMENT FRAUD: PRESSURE DAN RATIONALIZATION (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015—2017) - Soejoto, Ezra Imanuel; Petronila, Thio Anastasia (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
The accounting information contained in financial statements is beneficial for stakeholders in economic decision making. However, it is not uncommon for the management to commit financial statement fraud because of pressure from internal and external parties, the opportunity to commit fraud, the reasons for cheating, or the ability to commit fraud. The objective of the study is to analyze the financial target, financial stability, external pressure, and rationalization can be used to detect financial statement fraud. The research was conducted on manufacturing companies with metals and the like sub-sectors, plastics and packaging, automotive and components, and food and beverages listed on the Indonesia Stock Exchange from 2015 to 2017. The number of samples used was 135 observation units and sample selection using purposive sampling. Data analysis method uses descriptive statistics and logistic regression analysis, with significant value (α) is 5%. The results show that financial target affected financial statement fraud, while financial stability, external pressure, and rationalization did not affect financial statement fraud.